Root exudates mediated resistance mechanism in chilli (Capsicum annuum L.)against root knot nematode (Meloidogyne incognita) - Santhosh, G; Narayana Swamy, G; Devindrappa, M; Nayak, D K; Shalem Raju, R; Lakshmana Reddy, D C; Naresh, P; Shivashankara, K S; Umamaheswari, R; Anjali, T (Journal of Horticultural Sciences, 2025)
Chilli is an economically important vegetable and spice crop in India, but its productivity is severely constrained by root-knot nematodes, particularly Meloidogyne incognita. In this study, root exudates of chilli were analyzed using gas chromatography–mass spectrometry (GC-MS) to elucidate resistance mechanisms. Ninety-nine recombinant inbred lines (RILs) were previously screened, and two resistant RILs (ACRIL 70 and ACRIL 90) along with two susceptible varieties (Arka Mohini and Arka Suphal) were selected. Resistant RILs inoculated with M. incognita exhibited higher proportions of nematicidal compounds such as 2,6-di-tert-butylbenzoquinone (12.42% and 6.75%), hexadecanoic acid (15.12% and 6.78%), (7,7-dimethyl-1,4-dioxo-2,3,4,5,6,7-hexahydro- 1H-inden-2-yl) acetic acid (4.62% and 5.05%), and heptadecane (0.70% and 0.38%) in ACRIL 70 and ACRIL 90, respectively. Notably, hexadecanal (10.72%) was detected only in inoculated ACRIL 90. In addition, 2,6-di-tert-butylbenzoquinone was present in uninoculated resistant RILs (6.12% and 5.33%). In contrast, these compounds were present at much lower levels or absent in susceptible varieties. Resistant rootstocks also showed higher levels of antimicrobial and phenolic compounds both before and after inoculation, whereas susceptible lines exhibited significantly lower responses. These findings highlight the biochemical basis of nematode resistance in chilli and provide a foundation for breeding nematode-resistant cultivars, contributing to sustainable and eco-friendly nematode management.
Keywords: Chilli; GCMS analysis; Resistant RILs; root exudates; root-knot nematode